Optimising the management of bipolar disorder - Mahmood, A; Ebmeier, K (Practitioner Medical Publishing, 2015)
The prevalence of bipolar disorder in primary care patients is estimated to be between 0.5 and 4.3%, with 9.3% having bipolar spectrum illness. As many as 38% of patients are treated exclusively in primary care. Accurate and timely recognition and assessment of often lifelong and disabling symptoms is essential for long-term engagement in treatment and support at primary care level. This can reduce the use of inpatient services and prevent long-term loss of function. This article updates our previous review, in light of the most recent NICE clinical guidance, published in 2014, which reflects advances in the treatment approaches for patients with bipolar disorder.